CREATION OF MIXED POLYFUNCTIONAL CATALYSTS FOR HYDRATION OF ACETYLENE IN VAPOR PHASE - Soatboev, Komiljon; Daddahodjaev, Abdulla; Egamberdiev, Elmurod (Educational Research in Universal Sciences, 2023)
The catalytic properties of various substances in the transformation of acetylene depend on the mechanism of activation of reagents and the reactivity of intermediate substances. Acetylene chemistry uses metal complexes, acid-base catalysts, salts, and metal catalysts. A complex of mercury, cobalt, palladium, rhodium, chromium, titanium and other metals acts as a catalyst in the reactions of acetylene in the liquid phase.